Protective action of Lactobacillus curvatus CRL705 on vacuum-packaged raw beef. Effect on sensory and structural characteristics - Castellano, Patricia Haydee (2010)
Lactobacillus curvatus CRL705 was examined for its effectiveness as protective culture in the biopreservation of vacuum-packaged fresh beef stored during 60 days at 2 °C. For this purpose, L. curvatus CRL705, producer of lactocin 705 and lactocin AL705, was inoculated on the meat surface (106 cfu g−1). This microorganism became the dominating population throughout the storage period controlling the growth of Brochothrix thermosphacta and spoilage lactic acid bacteria naturally present on the meat. When the microstructural characteristics of the meat were evaluated using light microscopy, beef samples inoculated with the bioprotective culture showed a 10 days delay for the appearance of tissue degradation signs. Sensory analysis demonstrated that beef samples treated with L. curvatus CRL705 only developed an “acid” off-flavor after 60 days of refrigerated storage, and no undesirable off-odors were found. Therefore, inoculation with this bacteriocinogenic strain would provide an additional hurdle to improve storage life of refrigerated vacuum-packaged beef without affecting its sensory and structural characteristics.